Peran Orang Tua Terhadap Penanganan Perilaku Anak Autis X di SMK 4 Padang - Syafri, Heru Pratama; Iswari, Mega (Jurnal Penelitian Pendidikan Khusus, 2021)
This study discusses the case stage that the author found in the State Vocational High School 4, Padang City, where there are parents who have autistic children. To describe the role of parents in handling the behavior of children with autism X, how parents handle hyperactive behavior of children with autism, tantrum behavior and throwing things, then the obstacles faced by parents in handling autistic child behavior and how parents deal with obstacles to handling children's behavior autism. This research uses a case study method which is included in a qualitative approach, the subjects of this study are parents, school teachers and therapists, so that all data can be collected by researchers using observation, interviews, and documentation. The results showed that the way parents handle hyperactive behavior is by always asking questions to therapy, finding out in books and articles about how to assist children with autism, and fostering good relationships with X and other family members, adjusting their life patterns from meal times, hours of sleep and hours of rest. Then the parent always controls the food because he can't eat chocolate. the efforts that have been described above as well as the obstacles and efforts in overcoming the obstacles faced. This can be seen through observations, interviews and documentation studies that the authors have described in the previous chapter